Unsupervised Virtual Reality-Based Exercise Program Improves Hip Muscle Strength and Balance Control in Older Adults: A Pilot Study - Kim, Jungjin; Son, Jaebum; Ko, Nayeon; Yoon, BumChul (Archives of physical medicine and rehabilitation, 2013)
To assess the effects of an unsupervised virtual reality (VR)-based exercise program on hip muscle strength and balance control in older adults. Controlled cohort repeated-measures experimental design, a pilot study. University research laboratory. Ambulatory older adults (N=32) from a local community. The VR group (n=18; mean ± SD, 68.28±3.74y; 4 men) completed the VR-based exercise program, whereas the remaining subjects in the control group (n=14; mean ± SD, 66.21±3.87y, 1 man) were asked to continue their daily routine for 8 weeks. Hip muscle strength was measured using a multimodal dynamometer, and ground reaction force using the backward stepping test and the results of the crossover stepping test were recorded using a force platform. The VR group showed significant improvement in hip muscle strength of the extensors, flexors, adductors, and abductors after 8 weeks (all P≤.001). However, no significant improvement was observed in the control group. The VR group had significantly greater ground reaction force on the backward stepping test (with eyes opened and closed) (all P<.005) and the crossover stepping test (with eyes opened and closed) (all P≤.001) compared with those at baseline. However, no significant improvement was observed in the control group. The VR-based exercise program includes the role of supervisor and feedback, which is important for older adults. Therefore, a VR-based exercise program may be a useful tool to improve decreased physical function in older adults as a home-based exercise.